CD4+CD25+Foxp3+ regulatory T cells regulate immune balance in unexplained recurrent spontaneous abortion via the Toll-like receptor 4/nuclear factor-κB pathway. Issue 12 (December 2020) - Qin, Shuang; Li, Li; Liu, Jia; Zhang, Jinrui; Xiao, Qing; Fan, Yujuan; Wei, Xiangcai
Objective: The present study aimed to evaluate the effects of cluster of differentiation (CD)4 + CD25 + forkhead box p3 (Foxp3) + regulatory T cells (Tregs) on unexplained recurrent spontaneous abortion (URSA) and the associated mechanisms. Methods: The proportion of CD4 + CD25 + Foxp3 + Tregs and inflammatory cytokine concentrations in the peripheral blood of women with URSA were measured by flow cytometry and enzyme-linked immunosorbent assay, respectively. CBA/JxDBA/2J mating was used to establish an abortion-prone mouse model and the model mice were treated with the Toll-like receptor 4 (TLR4) antagonist E5564 and the TLR4 agonist lipopolysaccharide. Results: The proportion of CD4 + CD25 + Foxp3 + Tregs was decreased and the inflammatory response was increased in women with URSA. In the abortion-prone mouse model, E5564 significantly increased the proportion of CD4 + CD25 + Foxp3 + Tregs, decreased the inflammatory response, and increased Foxp3 mRNA and protein expression. Lipopolysaccharide had adverse effects on the abortion-prone model. Conclusions: These data suggest that CD4 + CD25 + Foxp3 + Tregs regulate immune homeostasis in URSA via the TLR4/nuclear factor-κB pathway, and that the TLR4 antagonist E5564 may be a novel and potential drug for treating URSA.